Optimal smooth consumption and annuity design - Bruhn, Kenneth; Steffensen, Mogens (Journal of Banking & Finance, 2013)
We propose an optimization criterion that yields extraordinary consumption smoothing compared to the well known results of the life-cycle model. Under this criterion we solve the related consumption and investment optimization problem faced by individuals with preferences for intertemporal stability in consumption. We find that the consumption and investment patterns demanded under the optimization criterion is in general offered as annuity benefits from products in the class of ‘Formula Based Smoothed Investment-Linked Annuities’.